Confucius at the Center of a Humanistic Discourse or "Cheng Hsuan Awakened from a Dream" - Wang, Ching-hsien (Surfaces, 1995)
This text is a poem translated by the author from Chinese into English. The annotations furnish information about the historical context to which the poem refers.